PENERAPAN METODE BERMAIN BERBANTUAN MEDIA JAM HURUF ABJAD DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA PADA KELAS II SD NEGERI 15 BANDA ACEH - Sezia Anesti; Aida Fitri; Hasniyati (STKIP Subang, 2026)
This research is motivated by the low initial reading ability of second-grade students of SD Negeri 15 Banda Aceh. This study aims to determine the improvement of teacher activity, student activity, and student learning outcomes through the application of the play method assisted by the alphabet letter clock media. This study uses a Classroom Action Research (CAR) approach which is implemented in two cycles, each of which consists of planning, implementation, observation, and reflection stages. The subjects of this study were all 37 second-grade students of SD Negeri 15 Banda Aceh, consisting of 16 female students and 21 male students. Data collection techniques were carried out through observation and performance tests, while data analysis used quantitative and qualitative descriptive techniques. The results of the study showed that teacher activity increased to reach the very good category. Student activity also increased significantly, as indicated by the increase in student activity, participation, and involvement in the learning process. In addition, student learning outcomes in initial reading ability increased from cycle I to cycle II, with an average value increasing from 79.08 to 90.03, and learning completeness reaching the very good category. This increase indicates that the application of the play method assisted by the alphabet letter clock media is able to create more active, interesting, and effective learning in improving students' initial reading skills. Based on the results of this study, it can be concluded that the application of the play method assisted by the alphabet letter clock media is effective in improving learning activities and initial reading skills of class II students of SD Negeri 15 Banda Aceh.